Proceedings of the 8th UPI-UPSI International Conference 2018 (UPI-UPSI 2018) 2019
DOI: 10.2991/upiupsi-18.2019.9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Work-Family Conflict, Marital Satisfaction And Job Satisfaction

Abstract: Work and family problems are important in the life of a nurse that causes conflict between work and family. This work-family conflict requires satisfaction in marriage and satisfaction in work. The purpose of this study is to examine the relationship between work-family conflict with marital satiction and between work-family conflict and job satisfaction. This research is survey research. The population in this study were nurses who worked in hospital X in Purwokerto with a sample of 40 people (men = 6 people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Work-family conflicts provide an effective contribution of 31.2% to marriage satisfaction. Research by Wulandari et al, (2019) also found a significant negative relationship between work-family conflict and marriage satisfaction; the more intense is the work-family conflict, the lower the perceived marital satisfaction.…”
Section: Jurnal Psikologimentioning
confidence: 93%
“…Work-family conflicts provide an effective contribution of 31.2% to marriage satisfaction. Research by Wulandari et al, (2019) also found a significant negative relationship between work-family conflict and marriage satisfaction; the more intense is the work-family conflict, the lower the perceived marital satisfaction.…”
Section: Jurnal Psikologimentioning
confidence: 93%
“…The second life domain in which work-family conflict has a relevant influence is within the family context and dynamics. Specifically, the most noteworthy family-related outcomes are marital satisfaction, family satisfaction, and family-related strain [23,38], which are all negatively affected by high levels of work-family conflict [39][40][41]. Indeed, when people are torn between work and family responsibilities, their ability to fully engage and participate in family life can be compromised.…”
Section: Family-related Outcomesmentioning
confidence: 99%
“…Outros estudos revelaram a existência de uma simbiose negativa entre o trabalho e os conflitos familiares com a satisfação familiar (Burch, 2020;Parasuraman & Simmers, 2001;Huang et al, 2004). De igual modo constatou-se a existência de uma associação negativa entre o trabalho e os conflitos familiares com o bem-estar psicológico (Lin et al, 2019;Obrenovic et al, 2020;Yucel & Fan, 2019) e uma relação negativa entre os conflitos laborais e as famílias com a satisfação conjugal (Aycan & Eskin, 2005;Jaenudim et al, 2020;Kim & Ling, 2001;Yucel, 2017a;Wulandari et al, 2019).…”
Section: Antecedentes E Consequentes Do Conflito Trabalho-famíliaunclassified